Characterization Of Porous Silicon And Zinc Oxide/Porous Silicon For Photodetector Application - Rosli, Nurizati (2018)
Zinc Oxide (ZnO) is widely used for the development of optoelectronic and electronic devices such as photodetectors, piezoelectric, field-effect transistors (FET), light emitting diodes (LED), photovoltaic, chemical sensors and others, because of its capability of fast response, high optical gain, high surface-to-volume ratio, and specific crystalline orientation. Meanwhile, porous silicon (PS) has drawn much attention for its application in the development of silicon-based optoelectronic devices due to its adjustable surface roughness and its ability to reduce the large mismatch in the lattice constants with the formation of porous layer. Merging both materials, the work is carried out to synthesize and characterize the properties of ZnO growth on PS. The PS substrates were prepared by using different parameter of etching time and current. It was found that, the etching condition is at current of 25 mA and 15 minutes etching time on n-type Si substrate with orientation (100) would achieve a uniform porous surface and good optical properties. Later, ZnO was sputtered onto the PS substrate by RF as a seed layer. The seed layer assists the nucleation of ZnO also promotes the growth development of ZnO wurtzite crystal structure along c-axis orientation. The different seed layer thickness of (50, 100, and 200) nm were sputtered. Then, the growth of ZnO structure was performed using chemical bath deposition (CBD) technique with different growth time of (1, 3 and 5) hours. Morphological analysis show that the grown ZnO microstructures covered randomly on and into the PS structure.